March: Book Two - Lewis, John, 1940-2020; Powell, Nate; Aydin, Andrew (Marietta, GA : Top Shelf Productions, 2015)
After the success of the Nashville sit-in campaign, John Lewis is more committed than ever to changing the world through nonviolence -- but as he and his fellow Freedom Riders board a bus into the vicious heart of the deep south, they will be tested like never before.
Keywords: Lewis, John, -- 1940-2020 -- Comic books, strips, etc; United States. -- Congress. -- House -- Biography -- Comic books, strips, etc; Student Nonviolent Coordinating Committee (U.S.) -- Biography -- Comic books, strips, etc; Lewis, John, -- 1940 February 21-; Student Nonviolent Coordinating Committee (U.S.); United States. -- Congress. -- House; Legislators -- United States -- Biography -- Comic books, strips, etc; African American legislators -- Biography -- Comic books, strips, etc; Civil rights workers -- United States -- Biography -- Comic books, strips, etc; African American civil rights workers -- Biography -- Comic books, strips, etc; African Americans -- Civil rights -- Comic books, strips, etc; Civil rights movements -- Southern States -- History -- Comic books, strips, etc; African American civil rights workers; African American legislators; African Americans -- Civil rights; Civil rights movements; Civil rights workers; Legislators; Southern States; United States; Autobiographical comic books, strips, etc; Graphic novels; Comic books, strips, etc; Graphic novels; History; Comic books, strips, etc